PENINGKATAN KREATIVITAS ANAK USIA DINI MELALUI KEGIATAN MELUKIS - Siti Kurniasih; Davina Kinanti Putri; Durotun Nasikhah (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2020)
This study is aimed at exploring the creativity skills improvement process of group B students in PAUD Nirmala and investigating to what extend the processing result of creativity skills can be improved through painting. This study was a classroom action research using Kemmis and Mc. Taggart research model. This study was conducted in 2 cycles with 8 meetings in each cycle where every cycle consisted of the following steps: planning, action and observation, reflection. The sample of this study was 14 Group B students comprissing of 6 male students and 8 female students. The instruments used in this study was observational sheet of students activities using paintings. The data in this study were quantitative and qualitative data. Quantitative data were analyzed by using descriptive statistic to compare the result from the first and second cycle. While qualitative data from field notes and interview were analyzed through the following steps: data reduction, data display and data verification. The results of this study show that there is the improvement of creativity through painting, proven by the creativity mean score in pre-cycle which was 50,17 % improve tso 67,50 % in cycle I and keep increasing becoming 86,29 % in cycle II. Keywords: Creativity, Painting, and Early Childhood